Stingless bee honey, a novel source of trehalulose: a biologically active disaccharide with health benefits - Fletcher, Mary T.; Hungerford, Natasha L.; Webber, Dennis; Carpinelli de Jesus, Matheus; Zhang, Jiali; Stone, Isobella S. J.; Blanchfield, Joanne T.; Zawawi, Norhasnida (Nature Publishing Group, 2020)
Stingless bee (Meliponini) honey has long been considered a high-value functional food, but the perceived therapeutic value has lacked attribution to specific bioactive components. Examination of honey from five different stingless bee species across Neotropical and Indo-Australian regions has enabled for the first time the identification of the unusual disaccharide trehalulose as a major component representing between 13 and 44 g per 100 g of each of these honeys. Trehalulose is an isomer of sucrose with an unusual α-(1 → 1) glucose-fructose glycosidic linkage and known acariogenic and low glycemic index properties. NMR and UPLC-MS/MS analysis unambiguously confirmed the identity of trehalulose isolated from stingless bee honeys sourced across three continents, from Tetragonula carbonaria and Tetragonula hockingsi species in Australia, from Geniotrigona thoracica and Heterotrigona itama in Malaysia and from Tetragonisca angustula in Brazil. The previously unrecognised abundance of trehalulose in stingless bee honeys is concrete evidence that supports some of the reported health attributes of this product. This is the first identification of trehalulose as a major component within a food commodity. This study allows the exploration of the expanded use of stingless bee honey in foods and identifies a bioactive marker for authentication of this honey in associated food standards.